The Role of Orientation on Labour Turnover. (A Case of Ghana Health Service) - Adu- Gyamfi, Augustine (2011)
A Dissertation Submitted to the Institute of Distance Learning, Kwame Nkrumah University of Sceince Technology, Kumasi, in Partial Fulfilment of the Requrements for the Award of a Common Wealth Executive Masters degree in Busness and Public Administration, May 2009